Factors Affecting the Income Curly Red Chili Farmers in Bocek Village, Karangploso Sub-District, Malang Regency - Zainol Arifin; Retno Ayu Novitawati; Farah Mutiara (Postgraduate, University of Mataram, 2024)
Bocek Village. once produced 1.650 tons of red chillies in 2017. However. the problem that farmers often complain about is price fluctuations. which affect farmers' income. Other factors are land area. production yields. and production costs. The purpose of this study was to analyze the level of income. feasibility and factors that influence red chili farming income. This research is a descriptive-quantitative study with a population of 207 farmers and a sample of 37 farmers determined through simple random sampling through a questionnaire instrument and analyzed using the revenue formula (total revenue = production obtained x selling price). production cost formula (total cost = fixed cost + variable cost) . the revenue formula (revenue = total revenue – total cost). and the feasibility formula (R/C). The results of the study stated that the average level of red chili farming income at the research location was 129.609.150 per year. This was obtained from an average total revenue of 178.647.297 and an average total production cost of 49.038.147 per season or per year. Furthermore. the results of this farming feasibility assessment were declared feasible based on the value of the ratio of revenues and production costs of 3.64> 1.